Pioneering versus Following the Promotional Behaviour of Lithuanian Innovative Companies - Pikturnienė, Indrė (Ekonomika, 2004)
Whether companies that enter markets with new products first appear at an advantage or disadvantage is still a questionable issue in theory and practice. The theoretical part of the working paper will demonstrate that empirical data are very controversial, and the number of fields is numerous where pioneers can gain advantages and disadvantages from being the first with a new product. The survey made in FebruaryApril 2004 aimed to examine how Lithuanian innovative companies perceived the distribution of advertising effort while creating a primary and secondary demand, and whether they perceived the pioneering to be advantageous or disadvantageous from the point of view of promotional and consumer education efforts.